A single session assessment and psychoeducational intervention for eating disorders: Impact on treatment waitlists and eating disorder symptoms - Fursland, A.; Erceg-Hurn, D.; Byrne, S.; McEvoy, Peter (John Wiley & Sons, Inc., 2018)
Objective: Long waitlists are common in eating disorder services and can have a detrimental impact on patients. We examined the effect on waitlist length, attendance, and eating disorder symptoms, of a 75–90 min single session intervention (SSI), attended a median of 16 days after referral to a specialist eating disorders clinic. Method: Sequential referrals (N = 448) to a public outpatient eating disorders program were tracked from referral until a decision was made on patients entering treatment. One group (“SSI cohort”) received a protocol incorporating assessment and psychoeducation about eating disorders before being placed on a waitlist, after which they received further assessment and entered treatment. Data on patient flow indices were collected from this cohort and compared to data from a “Pre-SSI” cohort who had not received the SSI. Symptom change was examined in the SSI cohort. Results: Waitlist length reduced and the proportion of referrals attending assessment and being allocated to treatment increased. Eating disorder symptoms and impairment decreased. Underweight patients (Body Mass Index [BMI] < 18.5 kg/m2) gained weight. Discussion: These findings suggest that a single session psychoeducational assessment may reduce waiting times, increase the likelihood of patients entering treatment, and facilitate early reductions in eating disorder symptoms. However, there may be other explanations for the changes observed.